MOTIVASI, BUDAYA ORGANISASI DAN LOYALITAS EFEKNYA TERHADAP KINERJA PEGAWAI DI KOMISI PEMILIHAN UMUM (KPU) PROVINSI BANTEN - Fatari, Fatari; Fidziah, Fidziah; Sarpia, Sarpia; Hartoko, Gatot (LP2M Universitas Bina Bangsa, 2024)
This research aims to determine the effects of organizational culture, loyalty and motivation on employee performance at the General Election Commission of Banten Province. This research uses a survey method and a quantitative descriptive approach. Data was collected by sending questionnaires to 36 people who answered. The Likert method and SPSS version 29 were used. The results of the research show that employee motivation, organizational culture and loyalty to work greatly influence their performance. The f-table value of 2.90 is less than 243.961, and the significance value of 0.001 is less than 0.05. Employee motivation, organizational culture and work commitment influence their performance at the Banten Province General Election Commission